Calcium leaching characteristics in landfill leachate collection systems from bottom ash of municipal solid waste incineration. (15th February 2021) - Li, Yuqian; Ma, Junwei; Ren, Yuqing; Li, Yijia; Yue, Dongbei
Abstract: Calcium leaching is a critical factor in the clogging of leachate collection systems (LCS), a phenomenon that affects landfill stability and operation. The bottom ash (BA) of municipal solid waste (MSW) incineration plants contains large quantities of calcium-based compounds. Landfilling is the main disposal method for BA in China that intensifies the consequences of LCS clogging. The factors influencing BA calcium leaching were investigated using simulated leachate. The results showed that fine BA particles, low pH values, high temperature, and ratios of leachate to BA solids were conducive to calcium leaching. Calcium leaching was found to be higher in actual leachate than in simulated leachate. At pH = 5, the cumulative calcium dissolution ratios (CDRs) were 83.36% and 31.49% after 20 days of leaching in the actual and simulated leachate, respectively; at pH = 6, the values were 50.67% and 12.06%, respectively. The introduction of landfill gas could decrease the calcium dissolution and leaching rates. When the ratio of leachate to BA solid was 20:1 mL/g, the accumulative CDR values were 45.98% (pH = 6) and 5.80% (pH = 8) without landfill gases, and 4.59% (pH = 6) and 0.48% (pH = 8) with landfill gases. These results provide the scientific basis for clogging risk prediction with respect to calcium leaching in the LCS of landfills. BA landfilling in old landfill areas with relatively high leachate pH and low chemical oxygen demand, as well as when leachate mixed with an appropriate amount of landfill gases, could be feasible measures to reduce calcium leaching and further prevent clogging in LCS. Highlights: The study investigated impacting factors of Ca leaching from bottom ash in leachate. Fine particle, low pH, high temperature and L/S ratio were conducive to Ca leaching. Ca leaching was higher in actual leachate than in acid simulated leachate. Landfill gas decreased Ca leaching rates from bottom ash in leachate.